Lungworm (Crenosoma vulpis) infection in dogs on Prince Edward Island. - Bihr, T (1999)
Crenosoma vulpis is a nematode lungworm that is highly prevalent in the red fox population of Atlantic Canada. Dogs are susceptible to infection with clinical signs consisting primarily of a chronic cough. A recent report of C. vulpis infection in 3 dogs on Prince Edward Island prompted an investigation into the importance of this parasite as a cause of chronic respiratory disease in Island dogs. A general prevalence was determined through the necropsy of dogs euthanized at the local humane society. Lungs were removed and examined for parasites using a lung flush technique. Rectal feces was collected and examined for first-stage larvae using the Baermann technique and zinc sulfate centrifugal flotation. Ten of 310 dogs (3.2%) were positive with 0-35 worms (mean = 11.0 +/- 13.4) recovered. First-stage larvae of C. vulpis were recovered in the rectal feces of the one animal in which no worms were recovered on lung flush. A second survey was conducted examining fecal samples with the Baermann technique from afebrile dogs with presenting signs of chronic cough that had no history of recent anthelmintic treatment and showed no signs of cardiac disease, based on physical examination. Fifteen of 55 dogs examined (27.3%) were definitively diagnosed as C. vulpis-positive. All of the infected dogs were treated with fenbendazole (50 mg/kg body weight, p.o. q24 h for 3-7 days). Clinical signs resolved in all of the dogs and fecal samples were negative 2-4 weeks posttreatment. It was concluded that C. vulpis infection was a significant cause of upper respiratory disease in dogs on Prince Edward Island and should be considered in all dogs with presenting signs of chronic cough.